2021
DOI: 10.1021/acsami.1c14945
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Polarity and Bulkiness of End-Functionalized Side Chains on the Charge Transport of Dicyanovinyl-End-Capped Diketopyrrolopyrrole-Based n-Type Small Molecules

Abstract: When designing organic semiconductors, side-chain engineering is as important as modifying the conjugated backbone, which has a significant impact on molecular ordering, morphology, and thus electronic device performance. We have developed three dicyanovinyl-end-capped donor–acceptor diketopyrrolopyrrole-based n-type small molecules (C2C9CN, SiC4CN, and EH4PCN) bearing an identical length of alkyl spacer yet different end-functionalized side chains (i.e., alkyl-, siloxane-, and phosphonate-end pendants). The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Phosphonate chain-end functionalized DPP copolymers were prepared by the synthesis procedures outlined in Scheme . Briefly, starting with DPP ( 1 ), bis­(2-ethylhexyl)­(4-bromobutyl)­phosphonate ( 2 ) prepared by the Michaelis–Arbuzov reaction was attached to the DPP core via base (potassium carbonate)-promoted N -alkylation, followed by dibromination with N -bromosuccinimide, yielding highly soluble DPP monomer with phosphonate chain-end solubilizing groups ( 4 ) (two-step overall yield = 23.5%). Polymerization via a palladium-catalyzed Stille coupling was performed by using 4 , bis-stannylated comonomers (Th-tin, Se-tin, TT-tin, and BT-tin in Scheme ), tris­(dibenzylidene­acetone)­dipalladium(0) [Pd 2 (dba) 3 ], and tri­( o -tolyl)­phosphine [P­( o -tolyl) 3 ] in anhydrous chlorobenzene under microwave heating at 140 °C for 3 h, thereby affording the desired copolymers EH4P-Th, EH4P-Se, EH4P-TT, and EH4P-BT as dark green solids.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphonate chain-end functionalized DPP copolymers were prepared by the synthesis procedures outlined in Scheme . Briefly, starting with DPP ( 1 ), bis­(2-ethylhexyl)­(4-bromobutyl)­phosphonate ( 2 ) prepared by the Michaelis–Arbuzov reaction was attached to the DPP core via base (potassium carbonate)-promoted N -alkylation, followed by dibromination with N -bromosuccinimide, yielding highly soluble DPP monomer with phosphonate chain-end solubilizing groups ( 4 ) (two-step overall yield = 23.5%). Polymerization via a palladium-catalyzed Stille coupling was performed by using 4 , bis-stannylated comonomers (Th-tin, Se-tin, TT-tin, and BT-tin in Scheme ), tris­(dibenzylidene­acetone)­dipalladium(0) [Pd 2 (dba) 3 ], and tri­( o -tolyl)­phosphine [P­( o -tolyl) 3 ] in anhydrous chlorobenzene under microwave heating at 140 °C for 3 h, thereby affording the desired copolymers EH4P-Th, EH4P-Se, EH4P-TT, and EH4P-BT as dark green solids.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, we examined the effects of polarity and bulkiness induced by phosphonate-end side chains on the optical and electrochemical properties, film microstructure, and charge-transport characteristics in a diketopyrrolopyrrole (DPP)-based small molecule platform in line with side-chain engineering considerations . Phosphonates are useful functional groups with a high polarity and bulkiness, which show a high compatibility with other organic functional groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these issues, many researchers have investigated various small molecules with highly ordered structures and strong intermolecular interaction by controlling the ordering of the molecules, thereby enhancing the charge transport between them. [30][31][32][33][34] By controlling the size and position of the alkyl chains and utilizing donor or acceptor moieties with high planarity and strong intermolecular interaction, molecular ordering between molecules can be improved.…”
Section: Introductionmentioning
confidence: 99%
“…Among the OSC molecules, much interest has been placed on thiophenes. ,,, One group of molecules with thiophene repeats, which has attracted much attention due to their high carrier mobilities and stable performance in OFETs and OPVs, is diketopyrrolopyrrole (DPP) derivatives. , A less investigated DPP derivative is the n -dialkyl side-chain-substituted thiophene DPP end-capped with a phenyl group (Ph-TDPP-Ph), which has a broadband absorption spectrum up to ∼650 nm and can be both solution-processed and vacuum-deposited, making it interesting for devices that require absorption over most of the visible spectrum. , One of the few studies on Ph-TDPP-Ph by Pickett et al investigated the correlation between the microstructure of Ph-DPP-Ph and charge transport in Ph-TDPP-Ph OFETs. The authors found that Ph-TDPP-Ph adopts two different crystalline phases in thin-film form, with one phase having significantly higher charge carrier mobility (by 2–3 orders of magnitude); however, it was not clear how to process the thin film in order to obtain the phase with the higher carrier mobility.…”
Section: Introductionmentioning
confidence: 99%